Military serious game federation development and execution process based on interoperation between game application and constructive simulators. (2015) - Choi, Changbeom; Seok, Moon-Gi; Choi, Seon Han; Kim, Tag Gon; Kim, Soohan
This paper proposes a development and execution process for military serious game federation, the military serious game federation development and execution process (MSGFDEP). The MSGFDEP utilises interoperation between an existing game application and constructive simulators to extend the serious game. In order to achieve the interoperation between the game application and constructive simulators, we use a high-level architecture (HLA). By interoperating a constructive simulator with an existing game application, a serious game developer can save efforts by extending a serious game application, rather than building a serious game from scratch. The proposed methodology is comprised of two specified process: federation development and federation execution. When the developer wants to build a serious game from scratch, the proposed methodology supports three specified processes: game loop analysis, game agent design, and development. On the other hand, when the developer wants to organise the federation with existing HLA-compliant serious game and constructive simulators, the methodology provides federation synthesis. Finally, the methodology defines the federation execution process to help trainees to obtain more experiences that are realistic.